2021
DOI: 10.1097/tp.0000000000003770
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Outcomes of Heart Transplant Recipients With Coronavirus-19 Disease in a High-volume Transplant Center

Abstract: Continuous values are presented as median (interquartile range) and categorical ones as n (%). COVID-19, coronavirus disease 2019; IQR, interquartile range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 30 publications
2
16
0
1
Order By: Relevance
“…Earlier studies have shown kidney, 7 , 10 , 21 lung, 26 , 27 and heart 28 transplant recipients to be at high COVID‐19 risk compared to non‐SOT patients, and liver transplant recipients to be at the same or lower risk than the general non‐SOT population for reasons unknown. 29 , 30 However, this is the first large‐scale analysis to compare COVID‐19 outcomes directly between different allograft types.…”
Section: Discussionmentioning
confidence: 98%
“…Earlier studies have shown kidney, 7 , 10 , 21 lung, 26 , 27 and heart 28 transplant recipients to be at high COVID‐19 risk compared to non‐SOT patients, and liver transplant recipients to be at the same or lower risk than the general non‐SOT population for reasons unknown. 29 , 30 However, this is the first large‐scale analysis to compare COVID‐19 outcomes directly between different allograft types.…”
Section: Discussionmentioning
confidence: 98%
“…Heart and lung transplant (HT/LT) recipients experience an elevated rate of severe illness due to SARS-CoV-2 infection ( 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ). While two SARS-CoV-2 messenger RNA (mRNA) vaccines are currently available, solid organ transplant recipients (SOTR) were excluded from Phase 1-3 trials ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although the study by Mohanka et al is small, it offers hope as outcomes are better than originally reported in lung transplant recipients. 4 , 5 , 19 , 20 , 21 Compared with earlier reports of mortality approaching 30%, in a more current series of 2307 solid organ transplant recipients with COVID-19 (8% lung transplant and 11% heart transplant recipients), 30-day mortality was 4.8%. 22 However, while the mortality of COVID-19 in lung transplant recipients may not be as high as originally feared, ongoing issues remain regarding the potential for long-term effects on allograft function, including acceleration of chronic allograft loss, as seen with other viral respiratory tract infections.…”
Section: Covid-19 In Lung Transplantationmentioning
confidence: 82%
“… 2 , 3 However, in subsequent reports, heart and lung transplant recipients fared worse than non-transplant patients, with an observed mortality of 20-30%. 4 , 5 Two articles in the current issue of the Journal of Heart and Lung Transplantation offer greater insight into the clinical characteristics and outcomes of heart 6 and lung 7 transplant recipients infected with SARS-CoV-2.…”
mentioning
confidence: 99%